0900 Chronotype and Social Support Among Student Athletes: Impact on Depressive Symptoms. (12th April 2019) - Wills, Chloe; Athey, Amy; Robbins, Rebecca; Patterson, Freda; Turner, Robert; Killgore, William D S; Tubbs, Andrew; Warlick, Chloe; Alfonso-Miller, Pamela; Grandner, Michael A
Abstract: Introduction: Previous studies have shown that chronotype is associated with depression scores, especially in young adults. But reasons for this are unclear. It is possible that students with later chronotypes are awake when others are sleeping, which can lead to social isolation. This study examined this relationship in a group of student athletes by examining relationships among chronotype, depression, and social support across multiple domains. Methods: Data were obtained from N=189 NCAA Division-I student athletes across all sports. Chronotype was assessed with a single item and ranged from -2 (definitely morning type) to +2 (definitely evening type). Depression was assessed with Center for Epidemiological Studies Depression scale. Social support was assessed with the Multidimensional Scale of Perceived Social Support, which included subscales for Family, Friends, and Significant-Other. A subscale for Team was created using the items from the Friends subscale (changing the word "friends" to "teammates"). Regression analyses adjusted for age, sex, and minority status. Results: Later chronotype was associated with more depression (B=1.01, 95%CI[0.18, 1.84], p=0.018). It was also associated with less social support overall (B=-3.31, 95%CI[-5.20, -1.42], p=0.001) and from family (B=-1.24, 95%CI[-1.92, -0.65], p<0.0001), friends (B=-1.06, 95%CI[-1.64, -0.48], p<0.0001), and team (B=-0.68, 95%CI[-1.21, -0.14], p=0.014). Chronotype-by-support interactions on depression were seen, such that the relationship between chronotype and depression were observed only in those with low (but not high) support from family, friends, and teammates. Conclusion: Later chronotype may be associated with social isolation, leading to decreased social support from family, friends, and teammates. (Significant others may be more likely to be present at these times, perhaps explaining a lack of findings in this domain.) This may contribute to the relationship to depression in college student athletes. Perhaps interventions aimed at reducing social isolation may reduce the impact of depression in students with later chronotypes. Support (If Any): R01MD011600, NCAA Innovations Grant